2015
DOI: 10.1016/j.metabol.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Does statin therapy reduce plasma VEGF levels in humans? A systematic review and meta-analysis of randomized controlled trials

Abstract: These results suggest a significant reduction in plasma VEGF concentrations following statin therapy. This effect depends on duration of treatment, LDL-lowering activity, lipophilicity of statins, and health status of studied individuals. Further RCTs are needed to explore if the VEGF reduction is implicated in the statin benefits on cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…However, notably, we adjusted our multivariable models for standard cardiovascular risk factors, rendering confounding by metabolic risk factors an unlikely explanation for our findings. Similarly, VEGF levels have been associated with statin intake 16. However, exploratory additional adjustment for statin intake had no relevant effect on our findings (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…However, notably, we adjusted our multivariable models for standard cardiovascular risk factors, rendering confounding by metabolic risk factors an unlikely explanation for our findings. Similarly, VEGF levels have been associated with statin intake 16. However, exploratory additional adjustment for statin intake had no relevant effect on our findings (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…However, it is unclear whether the association is due to confounding or reverse causation because VEGF may be a symptom of acute myocardial infarction . VEGF is pharmacologically modifiable, so assessment of its potential as a target of intervention for CVD prevention is important, and clarifying its etiological role may improve understanding of CVD. Trials have shown that statins lower VEGF, raising the possibility that one of the additional benefits of statins may be due to effects on VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is pharmacologically modifiable, so assessment of its potential as a target of intervention for CVD prevention is important, and clarifying its etiological role may improve understanding of CVD. Trials have shown that statins lower VEGF, raising the possibility that one of the additional benefits of statins may be due to effects on VEGF. Little evidence from randomized controlled trials concerning the effects of VEGF on CVD in the general population is available.…”
Section: Introductionmentioning
confidence: 99%
“…It is an exploratory study in two small cohorts with no reference to quantitative funduscopy such as OCT parameters. Moreover, we failed to match patients for statin use, which has been shown to moderately reduce VEGF-A levels [10]. However, both groups, controls and patients, where comparable in terms of daily and seasonal VEGF fluctuations, which argues against a major effect of statins on the results in our patients.…”
Section: Discussionmentioning
confidence: 88%